Gone with the wind - Gable, Clark 1901-1960.; Leigh, Vivien 1913-1967.; Howard, Leslie 1893-1943.; DeHavilland, Olivia; Selznick, David O. 1902-1965.; Howard, Sidney Coe 1891-1939.; Mitchell, Margaret 1900-1949.; Fleming, Victor 1883-1949.; Selznick International Pictures; Metro-Goldwyn-Mayer.; MGM/UA Home Video (Firm). ([New York] MGM/UA Home Video, 1990)
An epic saga of the south during and following the civil war.
Distributed in the Philippines by Warner Home Video (Phils.)
Based on the novel by Margaret Witchell.
Originally produced as a motion picture in 1939.
Music, Max Steiner.
Clark Gable, Vivien Leigh, Leslie Howard, Olivia DeHavilland.
DVD
Keywords: O'Hara, Scarlett (Fictitious character) -- Drama; Plantation life -- Drama; Reconstruction (U.S. history, 1865-1877) -- Drama; United States -- History -- Civil War, 1861-1865 -- Drama; Georgia -- History -- Civil War, 1861-1865 -- Drama; Film adaptations; Feature films; Historical films; War films